Keluarga Nirkekerasan sebagai Prasyarat Keluarga SakÃ®nah - Makmun, Moh. (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2015)
The article tries to redefine the meaning of sakÃ®nah family by emphasizing the importance of understanding the essence of marriage and domestic violence, which leads to criminal action, for spouse. Marriage is a social contract and agreement between a man and a woman, which aims at legalizing sexual interaction, making familial relationship through marriage, ensuring oneâs descendant, making a family, and living life together. Criminal action within marital relationship is any action committed by each spouse over another that violates laws, any action that harms his/her spouse physically, physiologically and economically, and/or a spouse who ignores his/her responsibility over another and over his/her children in the domestic sphere. SakÃ®nah family is a family which build on the basis of faith and piety upon God, a family whose breadwinner is able to fulfill the needs of family members based on his ability, a family which lives harmoniously and peacefully, a family which possesses ability and capability to overcome any conflicts among its members, a family with no violence and domestic crime, and a family whose members play their role respectively.